2002
DOI: 10.1021/jp020069o
|View full text |Cite
|
Sign up to set email alerts
|

Lateral and Vertical Quantification of Spin-Coated Polymer Films on Silicon by TOF-SIMS, XPS, and AFM

Abstract: PMMA and PVC were spin coated on silicon wafers using a range of polymer concentrations. This resulted in a corresponding range of film thicknesses and, for ultrathin film layers, various degrees of surface coverage. The thickness was determined by AFM profilometry and was used to correlate the time scale of a dynamic TOF-SIMS depth profile analysis to a depth scale. The degree of surface coverage was determined from AFM imaging and was used to correlate polymer secondary-ion yields of a static TOF-SIMS analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…The characterization of polystyrene oligomers (PS) on etched silver by 10 keV monoatomic Ar ϩ projectiles showed that the maximum yields were obtained when PS was prepared as a monolayer [11]. Other experiments performed with PMMA and PVC polymers led to similar conclusions [12]. The common factors for the aforementioned experiments were the use of coatings on specific substrates, in combination with an atomic projectile for analysis.…”
mentioning
confidence: 88%
See 3 more Smart Citations
“…The characterization of polystyrene oligomers (PS) on etched silver by 10 keV monoatomic Ar ϩ projectiles showed that the maximum yields were obtained when PS was prepared as a monolayer [11]. Other experiments performed with PMMA and PVC polymers led to similar conclusions [12]. The common factors for the aforementioned experiments were the use of coatings on specific substrates, in combination with an atomic projectile for analysis.…”
mentioning
confidence: 88%
“…The concentration of the spin-coated PS solution was 1 mg/mL and ellipsometric measurements indicate that the layer thickness is in the range 3-4 nm for those samples ( Table 1). The thickness values indicate that for 1 mg/mL, PS forms a monolayer coverage [11,12]. The mass spectra represent the intensity variation of the Au-cationized molecular ion, (M ϩ Au) ϩ , for PS spin-coated on Si and metallized with 0.5 nm Au (a), PS metallized with 6 nm Au (b), and PS spin coated on Au substrate (c).…”
Section: Mass Spectra Of Ps Monolayersmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of a SF 5 + cluster ion as a depth profiling etch tool for use on polymeric samples has been demonstrated by Fuoco et al employing PMMA thin film on silicon [13], Norrman et al also used PMMA and poly(vinyl chloride) films spin coated onto Si wafer [14] and by Mahoney et al who investigated poly(L-lactic acid) (PLLA) doped with 4-acetaminodophenol [15] and PLLA blended with a triblock co-polymer [16]. Most recently, with the introduction of the Buckminsterfullerene (C 60 ) cluster ion source as an etch tool, the depth profiling of polymeric (or organic) materials has taken great strides forward.…”
Section: Introductionmentioning
confidence: 99%